Temporal variability in tree responses to elevated atmospheric CO2. (9th January 2021) - Lauriks, Fran; Salomón, Roberto Luis; Steppe, Kathy
Abstract: At leaf level, elevated atmospheric CO2 concentration (eCO2 ) results in stimulation of carbon net assimilation and reduction of stomatal conductance. However, a comprehensive understanding of the impact of eCO2 at larger temporal (seasonal and annual) and spatial (from leaf to whole‐tree) scales is still lacking. Here, we review overall trends, magnitude and drivers of dynamic tree responses to eCO2, including carbon and water relations at the leaf and the whole‐tree level. Spring and early season leaf responses are most susceptible to eCO2 and are followed by a down‐regulation towards the onset of autumn. At the whole‐tree level, CO2 fertilization causes consistent biomass increments in young seedlings only, whereas mature trees show a variable response. Elevated CO2 ‐induced reductions in leaf stomatal conductance do not systematically translate into limitation of whole‐tree transpiration due to the unpredictable response of canopy area. Reduction in the end‐of‐season carbon sink demand and water‐limiting strategies are considered the main drivers of seasonal tree responses to eCO2 . These large temporal and spatial variabilities in tree responses to eCO2 highlight the risk of predicting tree behavior to eCO2 based on single leaf–level point measurements as they only reveal snapshots of the dynamic responses to eCO2 . Abstract : This review describes overall trends, magnitude and drivers of leaf‐scale and whole‐tree‐scale responses to rising atmospheric CO2 concentration. Results encourage frequent monitoring, as single point measurements provide a limited snapshot of dynamic tree functioning under future CO2 growing conditions.